STUDENTS’ AND TEACHERS’ PERCEPTIONS OF THE CAMBRIDGE CURRICULUM IMPLEMENTATION IN ENGLISH SUBJECT AT AN SPK SCHOOL IN SURABAYA - Data, Aga (Esteem Journal of English Education Study Programme, 2025)
This study explores students’ and teachers’ perceptions, along with contributing factors, toward the implementation of the Cambridge curriculum (TCC) in an SPK school in Surabaya. Using a mixed-methods approach with a descriptive design, data were gathered from 195 students and 4 teachers. The results from questionnaires and interviews indicate generally positive perceptions, with mean scores of 3.96 for students and 4.28 for teachers. Despite this, several challenges emerged, such as students’ difficulty in understanding Cambridge textbooks and differing views on infrastructure particularly Wi-Fi access and the presence of a language laboratory. Key factors influencing curriculum implementation include teacher adaptability, engagement from both students and teachers, curriculum flexibility, collaborative learning, and ICT integration. These findings provide valuable insight for SPK schools in Indonesia to assess and enhance their English curriculum practices. The study contributes to a better understanding of how international curricula are perceived in local contexts and offers practical considerations for improving teaching and learning strategies under the TCC framework.